Pengaruh Komite Audit, Biaya Lingkungan, Modal Intelektual, Likuiditas, dan Pertumbuhan Perusahaan terhadap Kinerja Keuangan Perusahaan - Almira Mahsa Zulaika; Desy Mariani (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of audit committees, environmental costs, intellectual capital, liquidity and company growth on company financial performance in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period totaling 126 companies. The data used in this study were obtained from financial report data and annual reports. The population in this study were food and beverage sector companies listed on the Indonesia Stock Exchange. The sampling technique used was the purposive sampling method and 160 sample data were obtained from 32 companies. The analysis technique used in this study is multiple linear regression analysis using IBM SPSS Statistics. The results of this study indicate that environmental costs and company growth have a positive and significant effect on the company's financial performance, while the audit committee, intellectual capital, liquidity do not affect the company's financial performance.